The politics of pessimism in Ecclesiastes: a social-science prespective - Sneed, Mark R. (Ancient Israel and its literature, 2012)
Introduction -- Qohelet's heterodox character : non-social science approaches -- Explaining Qohelet's heterodox character : social science approaches -- Qohelet's socio-historical context -- Qohelet and his audience's social location -- Synchronic (literary) analysis of the book of Qohelet -- Qohelet, the problem of evil, and cognitive dissonance -- Qohelet's irrational response to the (over-)rationalization of traditional -- The positive power of Qohelet's pessimism -- The sociology of the book of Qohelet's canonicity -- Conclusion